Code-switching costs from Chinese-English relative clauses processing - Hu, Wanying; Zhao, Yang (Frontiers in Psychology, 2023)
The source of costs is one of the main concerns in code-switching, but there is still no agreement. This study examines whether syntactic processing with code-switching produces the cost in Chinese-English dual languages. We use Chinese and English relative clauses in either object (Experiment 1) or subject (Experiment 2, which has a more complex structure) positions to test the costs in syntactic processing. Forty-seven Chinese-English bilinguals and sixteen English-Chinese participate in acceptability judgment tests and self-paced reading experiments. The results demonstrate that syntactic processing is one source of code-switching costs by revealing code-switching costs from the head movement processing in relative clause comprehension. The outcomes are consistent with the implications of the 4-Morpheme model and Matrix Language Framework. Additionally, the experiment shows that the processing of relative clauses depends on the underlying structures, which is consistent with the Dependency Locality Theory.